Food crisis risk monitoring: Early warning for early action - Vos, Rob; Husain, Arif; Greb, Friederike; Läderach, Peter; Rice, Brendan (International Food Policy Research Institute, 2023)
Global and national agrifood systems are vulnerable to a variety of shocks that have caused major disruptions to food production, markets, and livelihoods over the past two decades, and have set back efforts to reduce poverty, food insecurity, and malnutrition. Currently, the world is contending with the global repercussions of the Russia-Ukraine war. In many countries, the impact of the war is compounded by local conflict, weather shocks, lingering effects of COVID-19, macroeconomic instability, and weak coping capacity. These concurrent crises have led to a sharp rise in both acute and chronic food insecurity since 2017, especially in developing countries. According to estimates from the United Nations agencies, chronic food insecurity — measured as the number of people with prolonged insufficient food energy intake — rose from around 573 million in 2017 to as many as 828 million in 2021. Acute food insecurity — measured as food deficiency affecting lives at any given point in time — almost doubled between 2016 and 2022, from 108 million people in 2016 to 205 million in 2022 in 45 food crisis countries. Estimates of the World Food Programme (WFP), which considers more countries, suggest that as many as 349 million people in 79 countries faced acute food insecurity in 2022.